Stock assessment of the horse mackerel, Trachurus indicus in the Gulf of Suez, Egypt - Mehanna, Sahar Fahmy (Indian Journal of Fisheries, 2011)
Otoliths were used to estimate age composition, growth rate and mortality rates of Trachurus indicus in the Gulf of Seuz. Age composition varied between sexes. The oldest males were five years old and the oldest females were four years old. Mean back calculated lengths at the end of each year of life were estimated for males and females. The von Bertalanffy Growth Equation was L, = 24.48 (1 , -0.41243 (t + 0..353I9 ) for males and L. = 22.26 (1 - e â€¢"â€¢’^6480 (t + 019341)) fo^ females. The mean total mortality coefficient "Z" determined by two methods was found to be 1.02 year ’ for males and 1.14 year ’ for females. The natural mortality coefficient was computed to be 0.35 year ’’ for males and 0.38 year ’ for females